MHD forced convective flow past a vertical plate: an automated solution approach - Mohamad Asimoni, Nor Raihan; Mohammad, Nurul Farahain; Mohd Kasim, Abdul Rahman; Shafie, Sharidan (AIP Publishing, 2018)
The forced convection flow in incompressible viscous fluid past a vertical plate is investigated with the effect of magnetic field. The governing equations are solved numerically using automated solution technique which is FEniCS. It is shown that the increasing of magnetic field strength lead to decrease the velocity but increase the temperature for cooled plate. Meanwhile for heated plate, increasing magnetic field strength lead to decrease the velocity and the temperature of the fluid.